A Highly Active Galam Wood Bark-derived Solid Acid Magnetic Catalyst with Properties Suitable for Hydrolysis Reaction - Abubakar Tuhuloula; Chairul Irawan; Yulia Nurul Ma'rifah; Vanessa Dwi Az-Zahra; Ancella Grancia Yuliana Sanjani; Iryanti Fatyasari Nata (ASEAN Journal of Chemical Engineering, 2025)
Galam wood is a specific plant that is distributed in Kalimantan, especially in lowland areas, shallow peat forests, and swamps. After removing the bark layer, galam wood becomes a valuable building material. The galam bark (GB) is a biomass waste that could be utilized as a solid acid magnetic catalyst (M-SA). Biomass-based solid acid catalysts have gained interest due to the need for sustainable and low-cost alternatives. Nevertheless, most of them have low reusability, poor acidity, or high production cost. To create carbon material, the GB was sized (± 60 mesh) and underwent hydrothermal treatment in the presence of sulfonic acid at 90 oC for 8, 10, and 12 h. Then, the carbon was impregnated by 10 mmol/L of iron (III) chloride hexahydrate for 5 h and calcined at 500 oC for 1 h. The solid acid magnetic catalyst (M-SA) was produced. Based on Field Emission Scanning Electron Microscope (FE-SEM) observation, the morphological structure of galam bark changes due to the delignification and carbonization processes. The X-Ray Diffraction (XRD) showed a 75% increase in crystallinity after delignification. Fourier Transform-Infrared (FT-IR) showed the presence of the -SO3H group at a wavelength of 1137 cm-1. The optimum sulfonation time was obtained for 8 h with an acid content of 0.710 mmol/g. The Energy Dispersive X-Ray (EDX) Analysis measurement showed the Fe and S content of 60.21% and 4.18% w/w, respectively. The highest total reducing sugar (TRS) hydrolysis was 1.345 mg/mL from the hydrolysis of 1% M-SA catalyst at 100 oC for 1 h. The stability of M-SA showed good performance for the 4th repeated use with a decrease of only 6.5%. Solid acid magnetic catalyst from galam bark has good acid catalyst specifications and has the potential to be developed.